Durable Purchases over the Later Life Cycle - Martin Browning; Thomas Crossley; Melanie Lührmann (Koç University-TÜSİAD Economic Research Forum (ERF), 2012)
We investigate the life cycle patterns of households’spending on medium value durables. We use panel data on expenditures on appliances and consumer electronics the British Household Panel Study between 1997 and 2008. In cross section, expenditures for appliances and consumer electronics decrease strongly as households age. We show that this is entirely attributable to cohort effects and that when such effects are properly modelled, expenditure on consumer electronics rises with age. We also document important demand effects of household composition, labour supply and health status.
Keywords: D12; 330; life cycle model; consumer behaviour; durables; Elektronisches Produkt; Produktlebenszyklus; Konsumentenverhalten; Dauerhafte Konsumgüter; Großbritannien